Tunable orbital angular momentum in high-harmonic generation - D. Gauthier; P. Rebernik Ribič; G. Adhikary; A. Camper; C. Chappuis; R. Cucini; L. F. DiMauro; G. Dovillaire; F. Frassetto; R. Géneaux; P. Miotti; L. Poletto; et al. (Nature Communications, 2017)
The controlled generation of extreme-ultraviolet beams with controllable topological charge has not been demonstrated. Here, Gauthieret al. report on the generation of extreme-ultraviolet optical vortices with femtosecond duration carrying a controllable amount of orbital angular momentum.